Performance Enhancement of Multiband MIMO Antenna Using Metasurface - Sharma, Rashbha (My University, 2024)
The advent of 5G wireless communication has opened a new world of applications such as the Internet of Things (IoT), remote healthcare, RFID, virtual reality (VR) as well as drone based deliveries. 5G technologies supporting various use cases have spurred unprecedented demand for compact devices supporting high data rates. To support such opulent use cases with high data rate demands, 5G networks use high-frequency spectrum bands to transmit data. However, high-frequency bands are more susceptible to interference from buildings, trees, and other obstructions. Therefore, 5G networks extensively rely on implementing MIMO technology to improve signal quality and data transmission speeds by increasing the count of antennas at both the transmitting and receiving ends. A MIMO antenna system can be defined as a wireless communication technology that uses multiple copies of signals to be transmitted and received through multiple antennas at the transmitter and receiver end. Thus, MIMO antenna systems improve communication quality by enhancing system channel capacity and exponentially improving the performance of communication systems without increasing spectrum resources and antenna transmission power. To design a MIMO antenna system, an inter-element distance equivalent to one half of the operating wavelength of the antenna (λ/2) is utilized in order to get uncorrelated copies of signals, But this inter-element distance results in a large size of the MIMO antennas. On the other hand, when the inter-element distance is decreased, the mutual coupling results in poor performance in terms of gain and isolation. Moreover, to support a multitude of applications, a multiband MIMO antenna is also equally essential. Therefore, designing a multiband MIMO antenna with a compact structure, high isolation, and high gain is still a challenge. This thesis studies a methodology to design compact multiband MIMO antennas and enhance their performance using metasurface. The design of metamaterial unit cells like munegative (MNG), epsilon-negative (ENG), and double-negative (DNG) and their implementation for enhancement of the radiation characteristics, as well as the compactness of MIMO antennas, have been explored. In this research work, initially, an antenna element covering multiple bands is designed which is extended to form a multiband MIMO antenna. Next, the design and loading of metamaterial unit cells onto the MIMO antenna are done to achieve enhanced performance and compactness. In this thesis, five different compact MIMO antenna structures equipped with metamaterials covering multiple bands in sub-6GHz and millimeter Wave range frequencies of 5G have been proposed. The first MIMO antenna is designed to simultaneously exhibit coverage in both the sub- 6GHz range and the mmWave range bands of 5G. The designed MIMO antenna comprises a modified W-shaped antenna element structure optimized using TCMA to support multi-band coverage. This antenna element is extended to form a 2×1 MIMO antenna. By conducting parametric analyses, a minimized inter-element distance of 0.125λ (8.8 mm) is selected. With this minimized inter-element gap, the MIMO antenna exhibits a poor isolation level (S12<- 11.97dB) in the sub-6 GHz range. A double-negative metamaterial-based isolator is designed to enhance inter-element isolation at a minimized gap, improving the MIMO antenna's compactness. So, in this design, a parasitic placement of double negative metamaterial unit cells is done to improve isolation without compromising the multiband operation. The proposed MIMO antenna with parasitically loaded double negative metamaterial-based isolator (called Meta-MIMO) covers both sub-6GHz (3.42-4.25GHz) and millimeter Wave (24.85- 26.501GHz) band of 5G with high isolation (S12<-16.92dB). The second MIMO antenna comprises of a slotted rhombus-shaped antenna element. It attains enhanced gain using a newly designed epsilon negative metasurface reflector layer. The slotted rhombus-shaped antenna element is also designed using TCMA and covers a wide range of sub-6 GHz bands (from 3.2 to 5.8 GHz). The slotted rhombus-shaped antenna is then extended to form a compact 2×1 MIMO antenna by optimizing the value of the inter-element distance to a minimal possible value of 0.10λ, here λ represents the resonating wavelength at frequency of 3.0GHz. However, at this small inter-element distance (0.10λ(=6.0mm)), the MIMO antenna exhibits low isolation (S12<-12.2dB) and a low gain of 1.18 dB. Therefore, an epsilon negative unit cell-based reflector has been designed to enhance gain and isolation at this minimized gap (0.10λ). The ENG reflector has a unique plus shape and provides a significant gain enhancement of 3 dB at a minimal height of 8.0mm. The plus-shaped ENG reflector equipped MIMO antenna (PS-ENG MIMO antenna) exhibits high isolation with S12<- 22dB (enhanced from -12.2dB to -22.0dB) for the entire resonating bandwidth (3.2-5.8GHz) and an enhanced gain of 4.82 dB (improved from 1.81dB to 4.82 dB) at a minimized height of 8.0mm (≈λ/8).The third MIMO antenna comprises modified rhombus-shaped antenna elements. The TCMA has been implemented to create unique antenna elements that provide wide bandwidth, covering the sub-6 GHz range ((3.2-5.8GHz)). This modified rhombus-shaped antenna element is utilized to form a compact, two-element MIMO antenna by optimizing the distance (between the MIMO antenna elements). However, this compact MIMO antenna (with a small interelement distance of 0.13λ≈7.89mm) exhibits poor isolation levels of S12<-10dB. Therefore, a newly designed mu-negative (MNG) metamaterial unit cell-based isolator is designed. By implementing the TCMA, the MNG isolator is loaded onto the MIMO antenna (forming MNGMIMO) to alleviate the effects of high mutual coupling without compromising the structure's compactness. This arrangement is similar to the placement of metamaterials as a neutralization line, as both the radiating elements of the MIMO antenna are connected via an MNG isolator. The final proposed MNG-MIMO exhibits enhanced wide band isolation of S12<-25.5dB (improved from -10.0dB to -25.5dB) as well as a broad bandwidth of 2600MHz with a compact volume of 990mm3. The fourth MIMO antenna is designed using double-negative metamaterial unit cells. A newly designed double-negative (DNG) unit cell is optimized to exhibit coverage of sub-6 GHz range. The DNG unit cell array is loaded inside a rectangular ring patch. Using the characteristic modes theory, the position of DNG unit cells is optimized to form the metasurface patch antenna (DNG antenna). Next, the proposed DNG antenna element is utilized to form a 2×1 MIMO antenna, backed by a partial ground plane with a U-shaped slot. The designed metasurface MIMO antenna covers wide range of sub-6 GHz bands with high isolation and a very compact volume of 720 mm3 . This design implements the metamaterials onto radiating elements to attain a miniaturized MIMO antenna that covers multiple bands ((4.9-6.4GHz)) with wideband high isolation (<-27.73dB for the entire operating bandwidth). The fifth MIMO antenna includes a multiband epsilon negative metasurface-based MIMO antenna for mmWave range applications. The MIMO antenna (E-MIMO) constitutes metamaterial antenna elements (ENGpatch), which are designed by placing a newly designed epsilon negative unit cell at the center of a slotted patch. The E-MIMO antenna is optimized such that, without additional isolation enhancement techniques, it covers a broad range of frequencies of mmWave range ((23.2 GHz to 30.64 GHz) and (37.5–43.75 GHz)) with a high isolation of S21<-20 dB with a compact dimension of 10mm×5mm as well. v All five MIMO antennas loaded with respective metamaterials exhibit enhanced compactness, broad bandwidth, high isolation, and multiband operation in the 5G spectrum. To assess the performance of all designed MIMO antennas CST Microwave Studio Suite simulation tool has been used. Subsequently, the radiation performance of fabricated MIMO antennas are experimentally characterized. Using a Vector Network Analyzer (VNA), the impedance performance of the MIMO antennas is measured and validated.
Keywords: MIMO Antenna; Metasurface; Multiband; Patch antennas; Sub-6GHz; 5G; mmWave